Effect of combined arsenic and lead exposure on their uptake and translocation in Indian mustard. (1st April 2021) - Yang, Wenlei; Luo, Liqiang; Bostick, Benjamin C.; Wiita, Elizabeth; Cheng, Youfa; Shen, Yating
Abstract: Phytoremediation makes use of hyperaccumulating plants to remove potentially toxic elements (PTEs) from soil selectively. Most researches examining hyperaccumulators focused on how they act on a single PTE contaminant. However, there is more than one kind of PTEs in most contaminated soils. Phytoremediation approaches could be less effective in environments containing multiple PTEs contaminants. Here we examine arsenic (As) and lead (Pb) accumulation in Indian Mustard ( Brassica juncea ) from solutions with one or both pollutants. Indian mustard accumulates As or Pb when exposed in the single liquid exposure of As or Pb, and the highest concentrations of As and Pb in Indian Mustard reach 1, 786 mg/kg and 47, 200 mg/kg, respectively. But the absorption efficiencies of As and Pb decrease (by >90% for As, and ∼10–30% for Pb) when both As and Pb are present. The translocation of As and Pb from the root to leaf is also impeded by 36%–88% for As and 55–85% for Pb when treated with both PTEs. In As and Pb co-treatment, significant negative correlations between As (V) and P and between Pb and other elements (including K, Mg and Ca) were found in Indian mustard. X-ray absorption near edge (XANES) spectroscopy and subcellular extraction experiments indicate that much of the accumulated Pb bound within lead phosphate particles, and often located within the cell wall. Pb could decrease the percentage of water-soluble As and increase protein combined As in subcellular levels within Indian mustard. Based on these data, we suggest that the competition between Pb and monovalent and divalent nutrients (e.g., Ca(II), Mg(II) and K(I)), and the formation of lead phosphates within cell walls play critical roles in decreasing As and Pb co-uptake efficiencies for Indian mustard. Graphical abstract: Image 1 Highlights: Soil pollution is not caused by a single but multiple potentially toxic elements. Complex As + Pb treatment decreases Indian Mustard uptake of As and Pb by 90% and 30%. Negative correlations with cations like K Ca and Mg decrease co-uptake of As and Pb. X ray absorption spectroscopy indicates Pb bounds in the cell wall as Pb phosphates. Uptake competition and phosphates residues decrease complex As + Pb phytoaccumulation.